A New Structural Transformation of the Public Sphere? An Introduction. (July 2022) - Seeliger, Martin; Sevignani, Sebastian
The political public sphere is important for democracy, and it is changing – this is how the quintessence of Jürgen Habermas's monumental study on The Structural Transformation of the Public Sphere (1989) could be summarized in simple words. In the fields of political sociology and social theory, history, but also research on social movements, cultural studies, and media and communication studies, his conception of the public sphere as a sphere mediating between the state and civil society has had a decisive influence on the debate about the potential of collective reason for modern democracy. In this introduction we give a short overview of Habermas's arguments on the rise and fall of the bourgeois public sphere, demonstrate the necessary link between the public sphere and democracy and, referring to the contributions to this special issue, sketch current transformations of the public sphere along three basic processes – digitalization, commodification, and globalization.